Mincle receptor in macrophage and neutrophil contributes to the unresolved inflammation during the transition from acute kidney injury to chronic kidney disease - Wang, Cui; Zhang, Yilin; Shen, Anran; Tang, Taotao; Li, Ning; Xu, Chuanhui; Liu, Bicheng; Lv, Linli (Frontiers in Immunology, 2024)
Background: Recent studies have demonstrated a strong association between acute kidney injury (AKI) and chronic kidney disease (CKD), while the unresolved inflammation is believed to be a driving force for this chronic transition process. As a transmembrane pattern recognition receptor, Mincle (macrophage-inducible C-type lectin, Clec4e) was identified to participate in the early immune response after AKI. However, the impact of Mincle on the chronic transition of AKI remains largely unclear. Methods: We performed single-cell RNA sequencing (scRNA-seq) with the unilateral ischemia-reperfusion (UIR) murine model of AKI at days 1, 3, 14 and 28 after injury. Potential effects and mechanism of Mincle on renal inflammation and fibrosis were further validated in vivo utilizing Mincle knockout mice. Results: The dynamic expression of Mincle in macrophages and neutrophils throughout the transition from AKI to CKD was observed. For both cell types, Mincle expression was significantly up-regulated on day 1 following AKI, with a second rise observed on day 14. Notably, we identified distinct subclusters of Mincle-high neutrophils and Mincle-high macrophages that exhibited time-dependent influx with dual peaks characterized with remarkable pro-inflammatory and pro-fibrotic functions. Moreover, we identified that Mincle-high neutrophils represented an "aged" mature neutrophil subset derived from the "fresh" mature neutrophil cluster in kidney. Additionally, we observed a synergistic mechanism whereby Mincle-expressing macrophages and neutrophils sustained renal inflammation by tumor necrosis factor (TNF) production. Mincle-deficient mice exhibited reduced renal injury and fibrosis following AKI. Conclusions: The present findings have unveiled combined persistence of Minclehigh neutrophils and macrophages during AKI-to-CKD transition, contributing to unresolved inflammation followed by fibrosis via TNF-α as a central pro-inflammatory cytokine. Targeting Mincle may offer a novel therapeutic strategy for preventing the transition from AKI to CKD.